PENINGKATAN PENGETAHUAN PETANI DALAM PEMBUATAN MIKROORGANISME LOKAL DI DESA BULOTALANGI - Kariri, Muhamad Bagus; Dharmawan, Leonard; Nurulhaq, Muhammad Iqbal; Djoefrie, Mochamad Hasjim Bintoro (Pusat Studi Pembangunan Pertanian dan Pedesaan (PSP3) dan Ilmu Pengelolaan Sumberdaya Alam dan Lingkungan (PSL), 2024)
ABSTRACT Bulotalangi Village has great potential in utilizing banana stump waste to produce Local Microorganisms (MOL), which are important organic decomposers in agriculture. The study aims to increase the knowledge of Bulotalangi Village farmers about making MOL from banana stumps through counseling activities. Extension involved 30 farmers, with pretest, lecture, demonstration, question and answer, and posttest methods. The results showed an increase in farmers' knowledge on various aspects of MOL, such as understanding, benefits, composition, how to make, how to use, and how to store. The average initial knowledge of 36.48% increased to 94.44% after counseling, with the highest increase in knowledge of MOL composition by 63.34%. The increase reflects the effectiveness of extension in deepening farmers' understanding. This increased knowledge is expected to enable farmers to utilize local resources more effectively, support sustainable agricultural practices, and address the underutilization of banana stump in Bulotalangi Village. This can encourage village government policies to focus on banana stumps MOL to enhance the welfare of farmers and rural communities through home yard utilization.